Styrax benzoin emulgel for burn wound healing: formulation, evaluation, and in vivo study - Sianipar, Erlia Anggrainy; Angel, Lifiana; Sagala, Reynelda Juliani (Penerbit Universiti Kebangsaan Malaysia, 2025)
Burn-wound mortality is high, affecting 180,000 annually based on WHO’s data in 2018, especially in low-to-middle-income countries. Antibiotic misuse leads to resistance, prompting the need for alternative treatments. Studies have shown the effectiveness of Styrax benzoin in wound treatment, highlighting the need to investigate the formulation and in vivo study for burn wound healing. This study aimed to determine the optimal Styrax benzoin emulgel formula and evaluate its effectiveness on burn wounds in mice. Styrax benzoin extract was analyzed using various chemical tests and LC-MS/MS. The optimal emulgel formula was determined using the simplex lattice design (SLD) method with variations in Hydroxypropyl Methylcellulose (HPMC) and carbopol 940 concentrations. An in vivo study measured burn wound reduction and was analyzed using one-way ANOVA and Tukey post hoc test. Chemical tests found the presence of alkaloids, tannins, triterpenoids, and flavonoids. LCMSMS analysis showed cinnamic acids and vanillin. The optimal emulgel formula, with a 2:1 ratio of HPMC to carbopol 940, demonstrated 4.954 s adhesion, 5.594 cm spreadability, and 314533.329 cPs viscosity. At a 10% concentration of Styrax benzoin ethanol extract, this emulgel achieved the highest burn wound healing rate of 75.83%, significantly reducing the wound area.